2011
DOI: 10.1111/j.1745-4557.2011.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweetness Equivalence of Different Sweeteners in Strawberry‐flavored Yogurt

Abstract: To successfully substitute sucrose for sweeteners, further studies must be carried out based on previous knowledge of sweetener concentration to determine the equivalent sweetness of such compounds. In this work, sweetness equivalence of strawberry-flavored yogurt with different sweeteners and/or their combinations (aspartame, acesulfame-K, cyclamate, saccharin, stevia and sucralose) and yogurt sweetened with 11.5% w/w sucrose was measured using the sensory magnitude estimation method. The sweetness concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 19 publications
2
29
0
4
Order By: Relevance
“…Probably the acidity of the product was a factor that interfered with the sweetness perception of the sweeteners derived from stevia leaf extract, by masking the sweetness. Reis et al (2011) reported that the acidity interfered with the sweetness perception in a study on equivalent sweetness in strawberry yoghurt. The concentration of each sweetener was calculated in equivalence of the ideal sweetness of sucrose in acerola nectar (80 g/L) and the sweetness power was defined as the number of times a compound is sweeter than sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Probably the acidity of the product was a factor that interfered with the sweetness perception of the sweeteners derived from stevia leaf extract, by masking the sweetness. Reis et al (2011) reported that the acidity interfered with the sweetness perception in a study on equivalent sweetness in strawberry yoghurt. The concentration of each sweetener was calculated in equivalence of the ideal sweetness of sucrose in acerola nectar (80 g/L) and the sweetness power was defined as the number of times a compound is sweeter than sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Cardoso et al (2004) obtained a similar result (678) for 8.3% sucrose in mate tea at 45 °C and a lower value (554) for 8.3% sucrose in mate tea at 6 °C. Moreover, Reis et al (2011) reported a lower value (388) for 11.5% sucrose in strawberry yogurt.…”
Section: Group Selectionmentioning
confidence: 95%
“…As for coffee and tea, Moraes & Bolini (2009) found 9.5% and 12.5% sucrose, respectively, for instant coffee and roasted ground coffee, and Cardoso et al (2004) found 8.3% sucrose for mate tea at 6 °C and 45 °C. With regard to yogurt, Reis et al (2011) obtained 11.5% sucrose for strawberry yogurt.…”
Section: Ideal Sweetness Determinationmentioning
confidence: 98%
See 1 more Smart Citation
“…This study concluded that the concentration of 4.5% of all sweeteners (0.045% stevia) was preferred in the following order: sucrose and stevia, sucrose, stevia (Lisak et al, 2011). Another sensory evaluation study examined the sweetness equivalence of various combinations of sweeteners in strawberry flavoured yogurt including stevia, aspartame, acesulfame-k, cyclamate, saccharin, sucralose and sucrose (Reis et al, 2011). Using the magnitude estimation method, sucralose was found to be the sweetest while the cyclamate/saccharin/stevia mixture scored low (Reis et al, 2011).…”
mentioning
confidence: 99%